Sensitivities for Bermudan options by regression methods - Denis Belomestny; Grigori N. Milstein; John G. M. Schoenmakers (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
In this article we propose several pathwise and finite difference based methods for calculating sensitivities of Bermudan options using regression methods and Monte Carlo simulation. These methods rely on conditional probabilistic representations which allow, in combination with a regression approach, for efficient simultaneous computation of sensitivities at many initial positions. Assuming that the price of a Bermudan option can be evaluated sufficiently accurate, we develop a method for constructing deltas based on least squares. We finally propose a testing procedure for assessing the performance of the developed methods.
Keywords: 330; American and Bermudan options; Optimal stopping times; Monte Carlo simulation; Deltas; Conditional probabilistic representations; Regression methods; Optionspreistheorie; Suchtheorie; Regression; Monte-Carlo-Methode; Theorie